Estimation of thermocouple measurement errors for the ceramic specimen surface temperature in thermal tests. (1st January 2012) - Sereda, Gennadiy; Shulyakovskiy, Andrey; Durieux, Olivier
Thermocouples are the most widespread measuring tool in thermal tests of rocket and space vehicles. In this paper, a new theoretical and computational method of methodological error estimation is developed. Being based on the two-dimensional transient heat transfer model this method is intended for thermocouple measurement of flat ceramic specimen surface temperature under one-sided heating. The error estimation results can be applied to full-scale models. Validity of the method is confirmed by the comparison of the theoretical and experimental data confirmed.